Peningkatan Efektifitas Pembelajaran Dikaji Dari SudutManajemen Kelas Dan Kompetensi Mengajar GuruDi MTs Ta'mirul Islam Surakarta - Nur Annisa, Azkia; , Dr. Sabar Narimo,MM, M.Pd (2016)
The purpose of this research are: (1) to determine how much influence the management class to increase the effectiveness of learning (2) to determine how much influence the competence of teachers to increase the effectiveness of learning (3) to determine how much influence classroom management and teacher competence on increasing the effectiveness of learning in Ta'mirul Islam Junior High School. This research is a descriptive research with quantitative approach to drawing conclusions through statistical methods. The population in this study were all teachers at Ta'mirul Islam Junior High School. Methods of data collection is questionnaire and documentation. Questionnaire first be tested to determine the level of validity and reliability. Test requirements analysis in the form of normality and linearity test, to engineering data analysis using multiple linear regression analysis, ttest, F- test, the coefficient of determination as well as the relative contribution and effective. The results of the regression analysis obtained regression equation line is Y = 10.280 + 0,710X1 + 0,700X2. The conclusion that can be drawn from this equation are: 1) "There is a classroom management influence on the interest of enhancing the effectiveness of learning" is acceptable. This is evident through hypothesis test (t test), indicating that tcount> ttable namely 3.490> 2.023 with significance probability value <0.05, namely 0.000 and effective contribution of 37.2% 2) "There is an effect of competence teaching teachers to increase the effectiveness of learning "can be accepted based on the hypothesis test (t test), which is known that tcount> ttable namely 3.351> 2.023 with significance probability value <0.05, namely 0.000 and effective contribution 35.6 %. 3) "There is the influence of classroom management and teaching competency of teachers to increase the effectiveness of learning" unacceptable demonstrated through F test, which indicates the value of Fcount> Ftable is 34.857> 3.238 and significant probability value <0.05 is 0.000 with a coefficient of determination (R2) of 72.8% while the remaining 31.2% is influenced by other variables outside of this study.